[Cu(N^N)(P^P)]+ complexes with 2, 2′:6′, 2′′-terpyridine ligands as the N^N domain. Issue 16 (26th March 2015) - Murray, Niamh S.; Keller, Sarah; Constable, Edwin C.; Housecroft, Catherine E.; Neuburger, Markus; Prescimone, Alessandro
Abstract : Synthesis, structural, NMR spectroscopic and photophysical properties of the first [Cu(N^N)(POP)] + complexes with 2, 2′:6′, 2′′-terpyridines as the N^N domain are described (POP = bis(2-(diphenylphosphino)phenyl)ether). Abstract : The first examples of [Cu(N^N)(POP)] + complexes (POP = bis(2-(diphenylphosphino)phenyl)ether) in which the N^N domain is a 2, 2′:6′, 2′′-terpyridine (tpy) ligand have been prepared and characterized; N^N = tpy, 5, 5′′-dimethyl-2, 2′:6′, 2′′-terpyridine (1 ), 4′-(4-tolyl)-2, 2′:6′, 2′′-terpyridine (2 ), 4′-(4- n propoxyphenyl)-2, 2′:6′, 2′′-terpyridine (3 ) and 4′-(4- n butoxyphenyl)-2, 2′:6′, 2′′-terpyridine (4 ). In solution, the tpy domain in each [Cu(N^N)(POP)][PF6 ] complex is C 2 -symmetric, consistent with either tridentate coordination or a low energy dynamic process involving bidentate ligands; for [Cu(2 )(POP)][PF6 ] and [Cu(4 )(POP)][PF6 ], the 1 H NMR spectra showed negligible change between 295 and 210 K. The single crystal structures of [Cu(tpy)(POP)][PF6 ] and [Cu(4 )(POP)][PF6 ] are presented. The asymmetric unit of [Cu(tpy)(POP)][PF6 ] contains two independent cations; in one the tpy ligand is tridentate and in the other, it is bidentate with the non-coordinated pyridine ring facing the Cu atom (Cu⋯N = 3.146(1) Å). In contrast, the solid-state structure of [Cu(4 )(POP)][PF6 ] features a [Cu(4 )(POP)] + cation containing a bidentate tpy-domain with the non-coordinated pyridine ring oriented with the N-atom facing away from the Cu atom; this conformation may be associated with inter-cation N⋯HC non-classical hydrogen bonds. The photophysical properties of [Cu(N^N)(POP)][PF6 ] with N^N = tpy or1–4 are described. In the solid state at room temperature, the compounds are poorly emissive. In solution, the emission behaviour is consistent with ligand dissociation. This is supported by 1 H and 31 P NMR spectroscopic data which show POP and [Cu(POP)2 ] + in solutions of aged samples; mass spectrometric data are consistent with the formation of [Cu(N^N)2 ] 2+ in these samples.